Study of the ascorbate-glutathione cycle in transgenic plants Nicotiana tabacum under abiotic stress conditions - Pristupa, Kristina V.; Kukulianskaya, Tatsiana A.; Khramtsova, Elena A. (Experimental Biology and Biotechnology, 2021)
We conducted a comparative analysis of biochemical parameters for the ascorbate-glutathione cycle in non-transgenic and transgenic Nicotiana tabacum, plants cultivated in heavy metal polluted soils. Transgenic plants had in their genome a bacterial acdS-gene encoding the 1-aminocyclopropane-1-carboxylate deaminase (ACC-deaminase) enzyme. The introduction of elevated concentrations of copper, chromium, and lead ions into the soil promotes induction of the acdS-gene expression and an increase in ACC-deaminase activity in transgenic plants. It was shown the content of ascorbic acid (АА), glutathione, ascorbate peroxidase (АРХ) and glutathione peroxidase (GP) and glutathione reductase (GR) increased in plants under abiotic stress.